Unveiling the Forces Shaping Natural Gas Demand in the European Union - Obadi, Saleh Mothana; Korček, Matej (International Journal of Energy Economics and Policy, 2025)
Following the Russian invasion of Ukraine, European Union (EU) saw a significant drop of over 30% in its natural gas imports from Russia. Despite this challenge, European Union managed to make up for the shortfall by increasing imports of liquefied natural gas (LNG), thus preventing any immediate shortages of this vital resource. While policymakers’ efforts are recognized, it’s important to highlight that the main driver behind these major changes in natural gas imports was the response of the market to price fluctuations. The surging prices effectively balanced the supply and demand, though they also notably contributed to a period of heightened inflation in European Union. Understanding the dynamics of supply and demand in the European’s natural gas market becomes crucial for grasping the current economic landscape. With existing gas import routes nearing their capacity limits, adaptability primarily stems from the demand side. Using applied regression models, we identified the key factors influencing natural gas consumption and changes in demand patterns. Our analysis revealed a significant decrease in demand sensitivity to temperature, as subsidy programs failed to completely offset the impact of higher prices for end consumers. The role of gas in power generation is playing ever more important role, emphasizing that substitution options in power generation, or the absence thereof, could potentially stress the gas market in the event of nuclear outages, aggressive coal phase-outs, or unfavorable conditions for renewable generation. This underscores the imperative for a continuous and robust expansion of new renewable generation sources.